Surgical complications and cardiovascular comorbidity – Substantial non-immunological confounders of survival after living donor kidney transplantation. Issue 2 (April 2019) - Khandoga, Andrej; Thomas, Michael; Kleespies, Axel; Kühnke, Lennart; Andrassy, Joachim; Habicht, Antje; Stangl, Manfred; Guba, Markus; Angele, Martin; Werner, Jens; Rentsch, Markus
Abstract: Background: Surgical complications following kidney transplantation compromise immediate graft survival. However, the role of early surgical complications in the impairment of long-term survival is not completely established due to various other influences, such as patient comorbidities. The purpose of this study was to characterize the impact of surgical complications and overlapping patient comorbidities on graft function and survival after living donor kidney transplantation (LDKT). Methods: Two groups of patients following LDKT between 1995 and 2014 with (n = 65) or without (n = 294) Clavien–Dindo grade 3 and 4 complications were analyzed. Type of surgical revision, graft and patient survival, general patient characteristics, pre-transplant renal function, immunosuppression, and immunological characteristics (HLA mismatch, panel-reactive antibodies, rejections) were determined. Post-transplant graft function as well as long-term graft and patient survival were quantified. Results: Graft survival was 84.4/97.6% (1y), 75.2/92.7% (3y), and 62.1/87.6% (5y) with/without surgical revision, patient survival was 95.3/99.3%, 90.0/97.5%, and 84.7/93.7%, respectively. Surgical revision was required in 18%, which affected graft survival (p = 0.008) to a comparable extent as pre-existing cardiopulmonary/-vascular disease. Initially impaired graft function recovered to an equal level without complications following surgical revision. Whereas pre-existing cardiopulmonary/-vascular disease affected graft loss and patient survival, surgical revision had no particular impact on patient survival. These observations were confirmed by Cox regression. Conclusion: Long-term graft survival following LDKT is independently impaired by both postoperative complications and cardiovascular comorbidities. Although both factors may interact, a complication-free postsurgical course may improve graft survival, thereby reducing the need for dialysis restart and enhancing long-term recipient survival.